2021
DOI: 10.3390/ijms22094589
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells in the Skin: Defenders of Integrity or Offenders in Inflammation?

Abstract: Mast cells (MCs) are best-known as key effector cells of immediate-type allergic reactions that may even culminate in life-threatening anaphylactic shock syndromes. However, strategically positioned at the host–environment interfaces and equipped with a plethora of receptors, MCs also play an important role in the first-line defense against pathogens. Their main characteristic, the huge amount of preformed proinflammatory mediators embedded in secretory granules, allows for a rapid response and initiation of f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 349 publications
(429 reference statements)
1
46
0
2
Order By: Relevance
“…They can produce a large array of mediators and respond to perturbations in their environment, leading to their involvement in several inflammatory disorders ( 11 , 12 ). Whilst the role of mast cells in acne is poorly understood, these cells are known to play important roles in the skin immune system ( 13 ). Furthermore, different resident and recirculating T cell subsets are also known to participate in immune surveillance of the skin ( 14 ) and might be involved in the initiation of the immune response in acne.…”
Section: Introductionmentioning
confidence: 99%
“…They can produce a large array of mediators and respond to perturbations in their environment, leading to their involvement in several inflammatory disorders ( 11 , 12 ). Whilst the role of mast cells in acne is poorly understood, these cells are known to play important roles in the skin immune system ( 13 ). Furthermore, different resident and recirculating T cell subsets are also known to participate in immune surveillance of the skin ( 14 ) and might be involved in the initiation of the immune response in acne.…”
Section: Introductionmentioning
confidence: 99%
“…As expected, ILC2 cells were clearly increased in CRE- or OVA-treated mice relative to those untreated mice ( Figure 2B ), while the increase did not reach statistical significance for CRE treatment because of the limited sample size ( P = 0.071). Studies have also provided evidence that mast cells were increased in skin lesions of patients with AD ( 32 , 33 ) and have suggested that mast cells may participate in maintaining barrier function and homeostasis ( 30 , 36 , 37 ). Thus, we specifically analyzed mast cells (CD45 + CD3 – FcεRI + cKit + cells) in the skin isolated from those CRE- or OVA-treated mice ( Figure 2C ).…”
Section: Resultsmentioning
confidence: 99%
“…Mast cells are known to be critical in the regulation of allergic diseases because of their preferential localization close to skin epidermis or at the site of the tissue mucosa where exposure to environmental antigens and chemicals often occurs ( 26 30 ). Mast cells have large numbers of granules, containing mediators like histamine, serotonin, proteases, and cytokines, and they can synthesize prostaglandins, leukotrienes, and cytokines, thereby initiating inflammatory immune responses ( 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been performed to elucidate the roles of MCs in the skin under steady and diseased conditions. MCs play both facilitating and regulatory roles in a context-dependent manner ( 9 13 ). So far, the interleukin (IL)-10-mediated mechanisms have mostly been investigated as the regulatory mechanisms of MCs.…”
Section: Introductionmentioning
confidence: 99%